Regulation of Human Chondrocyte Function through Direct Inhibition of Cartilage Master Regulator SOX9 by MicroRNA-145 (miRNA-145) - Martinez-Sanchez, Aida (American Society for Biochemistry and Molecular Biology, 2012)
Articular cartilage enables weight bearing and near friction-free movement in the joints. Critical to its function is the production of a specialized, mechanocompetent extracellular matrix controlled by master regulator transcription factor SOX9. Mutations in SOX9 cause campomelic dysplasia, a haploinsufficiency disorder resulting in severe skeletal defects and dwarfism. Although much is understood about how SOX9 regulates cartilage matrix synthesis and hence joint function, how this master regulator is itself regulated remains largely unknown. Here we identify a specific microRNA, miR-145, as a direct regulator of SOX9 in normal healthy human articular chondrocytes. We show that miR-145 directly represses SOX9 expression in human cells through a unique binding site in its 3′-UTR not conserved in mice. Modulation of miR-145 induced profound changes in the human chondrocyte phenotype. Specifically, increased miR-145 levels cause greatly reduced expression of critical cartilage extracellular matrix genes (COL2A1 and aggrecan) and tissue-specific microRNAs (miR-675 and miR-140) and increased levels of the hypertrophic markers RUNX2 and MMP13, characteristic of changes occurring in osteoarthritis. We propose miR-145 as an important regulator of human chondrocyte function and a new target for cartilage repair.